THE DEVELOPMENT OF ISLAMIC ECONOMIC LAW IN INDONESIA - Januardi Tua Panjaitan, Tulus (Proceeding International Seminar of Islamic Studies, 2023)
The ideals of economic law are in line with the ideals of Islamic law contained in the maqᾱṣid asy-shari'ah with the focus on building and creating the benefit of the world and the hereafter for mankind. The ideals of Islamic law in the economic field can be seen in its concept of economic activity seen as a vehicle for society to lead to, at least, the implementation of the two teachings of the Qur'an. The development of Islamic economic law is basically parallel to other conventional economic law. With regard to an economy based on Islam, it is obligatory for Muslims in particular and is an alternative solution for non-Muslims. The existence of Islamic economics in general in Indonesian society is conceptually in accordance with the demands of the times. The Islamic finance industry in Indonesia has been recognized and implemented by the public. The existence of the Islamic economy is marked by the proliferation of Islamic-based financial institutions, one of which is sharia fintech.